Effects of daily administration of porcine somatotropin on performance of growing pigs (55 to 130 lb) - G E Fitzner; T L Weeden; B J Healy; B R Schricker; Robert H Hines; Jim L Nelssen; Robert D Goodband; Donald H Kropf; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1990)
Sixty crossbred barrows initially weighing 55.7 lb were used to evaluate six experimental treatments during a 5-wk growth trial. Pigs received one of three levels of dietary lysine (1.0, 1.5, or 2.0%) and were injected daily with either 3 mg porcine somatotropin (pST) or placebo. During the first 2 wk of the trial, there was no effect from either pST injection or increasing level of dietary lysine on average daily gain (ADG) or average daily feed intake (ADFI). Also, there was no effect of pST injections on feed conversion (F/G), but those pigs fed diets containing higher levels of lysine showed improved F/G. During the entire 5-wk period, pigs administered pST gained faster than placebo-injected pigs. During the 5-wk trial, there was a nonsignificant reduction in ADFI for pigs injected with pST compared with those receiving placebo injections. Increasing the level of dietary lysine also resulted in a nonsignificant reduction in ADFI. Pigs injected daily with pST showed a 10% improvement in (F/G) when compared with placebo-injected pigs. Increasing the dietary lysine level from 1.0 to 2.0% resulted in a 10% improvement in F/G for both pST- and placebo-injected pigs. Tenth rib fat depth and average backfat thickness were both reduced in pST-treated pigs compared with placebo-injected pigs.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; GF; Repartition; Performance; Lysine